Composição e estrutura da assembleia de larvas de peixes em um trecho lótico remanescente do Rio Paraná, na região do Parque Nacional de Ilha Grande - Brasil - Gogola, Tatiane Mary (2010)
The study of initial stages of the lifecycle of the fish is important for understanding the success of species in the environment and determine areas and spawning periods. This study analyzed the composition and structure of the assembly of fish larvae in a region of the last lotic stretch of the Paraná River at Ilha Grande National Park, searching for differences in spatial and temporal patterns of abundance, richness, diversity of larvae and indicator taxa and to examine the possible influence of some abiotic factors on the catch. Samples were taken monthly at night and six consecutive breeding seasons (October-March) between 2001 and 2008 (periods I, II, III, IV, V and VI) in three different environments (river, lake and tributaries). To this end, we used networks of conical-cylindrical plankton mesh 0.5 mm, equipped with a flowmeter to obtain the volume of filtered water. Simultaneously to the data were obtained at water temperature, dissolved oxygen, electrical conductivity and pH. Besides these, were also obtained data on the river level and rainfall. Was determined, besides the abundance of larvae, the number of species (richness), the diversity index of Shannon and the specific indicator taxa for each environment and periods analyzed using the indicator value (IndVal). To determine whether there were significant differences between the biotic, was applied to analysis of variance of main effects (ANOVA, one-way) and Tukey's test, modified for number of elements between different groups (Unequal) to determine which levels differed. To assess the relationship of environmental variables and abundances was applied to multiple regression analysis. The assemblage of fish larvae of the National Park of Ilha Grande was composed for the most part by bodies covered by the order Characiformes. Periods I and IV were the highest density of larvae, while the latter showed the highest richness and diversity of species. The indicator species of the periods were mostly sedentary, but Rhinelepis aspera and Salminus brasiliensis, captured in the (V and I, respectively) higher river level and rainfall. Between environments, pond was significantly different from tributaries and the catches were quite high, with high wealth and low diversity. Among indicator species of this environment, we find migratory and non migratory species. The House of larvae was related to water temperature, pH, dissolved oxygen, river level and rainfall. It was then possible to observe the existence of spatial and temporal differences in assemblage structure and composition of larvae in the region of the Ilha Grande National Park, mainly related to the characteristics of the study sites and environmental factors. It was observed further that lentic provided favorable characteristics for development of both sedentary species as migratory, while the tributaries are apparently being used as a migratory route and spawning areas due to capture of newly hatched larvae, demonstrating the importance of adopting measures to protect these types of environment, not only in the region of Ilha Grande National Park, but throughout the remainder of the lotic stretch of the floodplain of the Paraná River.